2015
DOI: 10.5897/jmpr2015.5931
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon bark water-infusion as an in-vitro inhibitor of -hematin formation

Abstract: Malaria remains one of the prominent public health problems that lead to severe morbidity and mortality in many developing countries around the globe. New antimalarial drugs are urgently needed due to the emergence of antimalarial-resistant strains of Plasmodium falciparum. In previous studies, we tested several plants extracts that are capable of inhibiting β-hematin formation, with efficiency similar to chloroquine. In the current study, the effect of cinnamon ethanol and water extracts on inhibiting β-hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Absorbance of the concentration series was measured at 310 nm. A graph of absorbance at 310 nm vs concentration of cinnamon extract was plotted (Akkawi et al, 2015). Absorbance of the supernatants which remained after the separation of the product containing pellets, were measured at 310 nm.…”
Section: Characterization Of Microparticlesmentioning
confidence: 99%
“…Absorbance of the concentration series was measured at 310 nm. A graph of absorbance at 310 nm vs concentration of cinnamon extract was plotted (Akkawi et al, 2015). Absorbance of the supernatants which remained after the separation of the product containing pellets, were measured at 310 nm.…”
Section: Characterization Of Microparticlesmentioning
confidence: 99%
“…20,21 Previous studies have shown that cinnamic acid affects the in vitro growth of Plasmodium falciparum and the permeability of the membrane of malaria-infected erythrocytes. 22 The administration of quercetin to animals undergoing acute stress suppressed activation of the hypothalamic-pituitary-adrenal (HPA) axis, which was a significant component of the stress response and played a major role in the aetiology of stress-related pathologies.…”
Section: Hplc Analysismentioning
confidence: 99%
“…Study done by Attieh A. Hanadi et. al set up that, cinnamon's crude watersoluble extracts capacity to suppress β-hematin configuration ( malaria pigment/ hemozoin) in vitro [7].…”
Section: Study Done By Yeti Nurhayati and Tresiamentioning
confidence: 99%